Over-the-counter procured emergency contraception among undergraduate students in a public University in Ghana - Fred Yao Gbagbo (Contraception and Reproductive Medicine)
Abstract Background Emergency Contraception (EC) is more popular among young people today, yet, there is little research on Over-the-counter procured EC among undergraduate students in African universities. This study's primary goal is to fill that gap. Methods This was an exploratory-cross-sequential study conducted in a public university in Ghana, using 145 purposively sampled sexually active undergraduate students. A structured questionnaire and in-depth interview guide designed by the author were used for data collection during the University’s 2021/2022 Academic year. The questionnaire was administered online via students’ social media platforms. In contrast, four group discussions were held with 20 female participants (5 each from levels 100, 200, 300, and 400). Quantitative data were analyzed using Stata Version 14.0 to generate the Median, Standard deviation, Chi-square, and Fisher Exact Test scores, Whilst Content analysis was done with the qualitative data to generate verbal quotes. Results There is demand and abuse of ECs among the students studied with about 99% usage to prevent pregnancy. Friends (81%) played a significant role in providing information about ECs to most participants (96%). About 80% of participants have used an EC at least once during the academic year and upon recommendation by friends (44%) and partners (39%). The most preferred ECs were Postinor-2 (61%) and Lydia post-pills (38%). Pharmacies on campus are the major (86%) suppliers at a cost between ghs5 and ghs15 cedis respectively. There were relationships between gender and choice of ECs (p = 0.001); age group and choice of ECs (p = 0.02); marital status and choice of ECs (p < 0.0001) as well as employment status of students and choice of ECs (p = 0.003). The qualitative findings provided relevant justifications for students’ EC choices, sources, dosage, frequency, and motivations for use. The EC pills were taken routinely and soon after sexual intercourse sometimes overdosed for a perceived efficacy to prevent failure, regulate menses, or as an abortifacient. Male partners played a critical role in procuring and supervising the intake soon after sexual intercourse. Conclusion There is a high demand, usage, and general abuse of over-the-counter procured ECs among undergraduate students in the study area. These findings suggest that sexually active students are concerned about pregnancy prevention and need health education programs on modern contraceptive methods to prevent unwanted pregnancy and possible STIs. From unprotected sex.